THE EFFECT OF NONI LEAF EXTRACT ON THE PHYSICAL COMPOSITION OF MALE BALI DUCKS - L. D. P. M., Here; Siti, N.W.; Puspani, E. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aimed to determine the effect of noni leaf extract on the physical composition of male Bali duck carcass aged 0-8 weeks. The study used a completely randomized design (CRD) with three treatments and five replications, each replication using two male Bali ducks with a body weight of 63.6 ± 1.96 g. The treatment given is; P0 (drinking water + without noni leaf extract), P1 (drinking water + 2ml noni leaf extract) and P2 (drinking water + 4ml noni leaf extract). The variables observed in this study were slaughter weight, carcass percentage, meat percentage, bone percentage, skin and fat percentage. The results showed that the administration of 2 ml and 4 ml of noni leaf extract had no significant effect (P>0.05) on slaughter weight, carcass percentage, meat percentage and bone percentage, but had a significantly different effect (P<0.05) on skin and fat percentage. . Based on this study, it can be concluded that the administration of noni leaf extract as much as 2ml-4ml/head/day did not have a significant effect on the physical composition of the carcass of male bali ducks.